Muhammadiyah Gerakan Islam Berkemajuan: Selayang Pandang - Muhammad Kahfi (SIASAT, 2019)
Muhammadiyah is a Progress Islamic movement that dares to bring out healthy and pure thoughts on the basis of al-'qurandan hadith. The term Islamic Progress is by developing the ethos of surah Al-'Ashr not just talking about the obligation to support the poor, but also the obligation to proceed to form the main civilization. The term Islamic Progress was first initiated by Kiai Ahmad Dahlan as the founder of Muhammadiyah in the early days of his struggle.